2018
DOI: 10.3389/fpls.2018.01346
|View full text |Cite
|
Sign up to set email alerts
|

The Fight Against Panax notoginseng Root-Rot Disease Using Zingiberaceae Essential Oils as Potential Weapons

Abstract: The root of Panax notoginseng (P. notoginseng) is one of the most highly valuable medicinal herbs in China owing to its pronounced hemostatic and restorative properties. Despite this important fact, growing P. notoginseng is seriously limited by root-rot diseases. In studies aimed at developing a solution to this problem, environment-friendly essential oils (EOs) of five medicinal plants of the family Zingiberaceae were tested for their inhibitory effects on the growth of three main soil pathogens associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…In the previous study, EOs from either Alpinia officinarum Hance and Amomum tsao-ko ( Zingiberaceae ) are found to have a good inhibition against the F. oxysporum , F. solani , and C. destrutans [26], and the EOs of Alpinia Katsumadai Hayata and Zingiber officinal Roscoe also have significant reductions in the mycelium growth of the pathogen in vitro [27]. This is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In the previous study, EOs from either Alpinia officinarum Hance and Amomum tsao-ko ( Zingiberaceae ) are found to have a good inhibition against the F. oxysporum , F. solani , and C. destrutans [26], and the EOs of Alpinia Katsumadai Hayata and Zingiber officinal Roscoe also have significant reductions in the mycelium growth of the pathogen in vitro [27]. This is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 89%
“…To simulate the antifungal effect of CEO in vivo, the growth of P. notoginseng was studied by adding CEO into the matrix. [24] Experimental studies in vivo showed that the disease incidence and index of F. oxysporum groups were higher than those of other groups, and the fresh and dry weights of the roots, stems and leaves were lower than those of the four groups. In particular, the weight of the roots was particularly low in the F. oxysporum group, indicating that F. oxysporum had a strong pathogenicity to P. notoginseng.…”
Section: Discussionmentioning
confidence: 97%
“…In brief, collected leaves were ground using liquid nitrogen, and SOD, POD, and MDA were extracted using the extraction buffer. The extracts were centrifuged at 12,000 × g for 10 min, and the supernatants were then measured for SOD, POD activities, and MDA contents using the multimode microplate reader (Tecan, Switzerland) ( Yin et al, 2018 ). Each indicator had three replicate measurements.…”
Section: Methodsmentioning
confidence: 99%